Wide local excision vs. Mohs Tübingen technique in the treatment of dermatofibrosarcoma protuberans: a two‐centre retrospective study and literature review. (3rd July 2017) - Veronese, F.; Boggio, P.; Tiberio, R.; Gattoni, M.; Fava, P.; Caliendo, V.; Colombo, E.; Savoia, P.
Abstract: Background: Dermatofibrosarcoma protuberans (DFSP) is a rare, low‐grade mesenchymal skin tumour, characterized by slow infiltrative growth and common local recurrence, with infrequent distant metastases. Objective: The aim of this study is to better clarify clinicopathological characteristics of this tumour and to evaluate the cure rates of Mohs Tübingen technique (MTT) and wide local excision (WLE). Eventually, we perform a literature review to compare our experience with published data. Methods: A retrospective review was conducted on 135 patients diagnosed, treated and followed up between 1997 and 2014 at two different institutions. Sixty‐two patients underwent to WLE and 73 to MTT. The primary end‐points were the following: percentage of recurrences, time to progression and recurrence annual risk rate. Then, the PubMed database was searched for DFSP case series treated with standard surgical resection (SSR), WLE, Mohs' micrographic surgery (MMS) and MTT. The annual risk rate of recurrence calculated and reported for the four separate procedures was pooled to compare them. Results: Five of the 62 patients with WLE (8.1%) experienced recurrences after a mean follow‐up of 4.7 years; the percentage of recurred patients 9 years after MTT was 5.5%, and the annual recurrence risk rate of 0.6%. Pooling these data with those from literature, the recurrence rate varies from 26% to 60% for SSR, from 0% and 41% for WLE, from 0% and 8.3% for MMS and from 0% to 5.5% for MTT. The lowest annual recurrence risk rate was found for MTT. Conclusion: Significantly lower recurrence rates were recorded in patients treated with classic or Tübingen Mohs' technique. To the best of our knowledge, our case series is the widest treated with MTT ever described in the literature; these data may be useful to guide clinicians in the choice of the gold standard treatment for Dermatofibrosarcoma protuberans.